Etiological structure of infectious agents in the urinary tract among children - Yeleupayeva, Sh.K.; Dinmukhamedova, A.S. (Fundamental and Experimental Biology, 2021)
The article presents the results of the research of etiological structure of urinary tract infection among children. Out of the total number of urological and nephrological sick children`s research, it is defined that 283 microorganisms selected from the urine were found. 63.2 % of the total number of children in nephrological department is related to only urological diseases. In recent, there has been an open trend to increase a frequency of diseases of the urinary system. Over the past five years, the number of diseases of the genitourinary system in urban children in Kazakhstan has increased to 65 %.The review shows that inflammatory diseases of kidneys and urinary tract take the second place after acute respiratory diseases of upper breathing tract. In this work, it is established that a causative agent of urinary system infection among children is pathogenic, as well as relative-pathogenic microorganisms. As it is shown, the leading etiological agent of uroinfection is Staphylococcus epidermidis (13.9 %), Escherichia coli (12.2 %), Enterobacter cloacae (7.8 %). In some cases, streptococcus are excreted. Also, there were dominant pathogens of nephroinfection among children such as Escherichia coli (21.1 %), Enterococcus faecalis (9.6 %), Staphylococcus epidermidis (20.1 %). Some types of Candidafungi in the formation of the urinary tract and kidney infection (mostly C.albicans (9.5 %), C.kruseae (8.1 %), C.glabrata (5.6 %) pathogens) are observed in the study of urine in children. During the general research, it was found that the etiological agents of urinary system among children consist of a huge microbiological spectrum, especially among children living in urban areas.